1999
DOI: 10.1038/sj.bjp.0702849
|View full text |Cite
|
Sign up to set email alerts
|

Receptor density as a factor governing the efficacy of the dopamine D4 receptor ligands, L‐745,870 and U‐101958 at human recombinant D4.4 receptors expressed in CHO cells

Abstract: 1 The relationships between the density of dopamine D 4.4 receptors and the agonist e cacies of L-745,870 (3-(4-[4-chlorophhenyl]piperazin-1-yl)-methyl-1H-pyrrolo [2,3-b]pyridine) and U-101958 ((1-benzyl-piperidin-4-yl)-(3-isopropoxy-pyridin-2-yl)-methyl-amine) were investigated in Chinese hamster ovary (CHO) cells, after treatment with the gene expression enhancer, sodium butyrate. 2 In CHO cells expressing D 4.4 receptors (CHO/D 4 cells), dopamine inhibited forskolin-stimulated cyclic AMP accumulation (E max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…This may be a peculiarity of rat, as opposed to human dopamine D 4 receptors. Even though we and others have reported agonist activities of U-101958 at human dopamine D 4 receptors (Gazi et al 1998(Gazi et al , 1999bSharma et al 1999), the similar activities of PD168077 and U-101958 are noteworthy. This finding shows that data on the human dopamine D 4 receptor should be extrapolated with caution to the rat equivalent.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This may be a peculiarity of rat, as opposed to human dopamine D 4 receptors. Even though we and others have reported agonist activities of U-101958 at human dopamine D 4 receptors (Gazi et al 1998(Gazi et al , 1999bSharma et al 1999), the similar activities of PD168077 and U-101958 are noteworthy. This finding shows that data on the human dopamine D 4 receptor should be extrapolated with caution to the rat equivalent.…”
Section: Discussionmentioning
confidence: 73%
“…At the rat dopamine D 4 receptor, these compounds acted as partial agonists (relative efficacy around 30%). Here again, although all three have been presented as antagonists (Patel et al 1997;Seeman et al 1997;Tallman et al 1997), we have found evidence that they can behave, at least under some circumstances, as partial agonists at the human dopamine D 4 receptor (Gazi et al 1998(Gazi et al , 1999a(Gazi et al , 1999b. For example, an increase in the expression of human dopamine 562 Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[177][178][179]; development of PET radioligands [180]; in D4 receptor-overexpressing cell systems [52,181]; tests for antipsychotic activity [120,182] L-741,742 3.5 In vivo administration to mice for anxiety testing [183] ABT 724 *45-65…”
Section: Dopamine-related Diseasesmentioning
confidence: 99%
“…Now, after several of these compounds have been tested and published, the issue remains controversial Patel et al 1997;Mansbach et al 1998). For instance U-101958, a prominent D 4 selective antagonist, was found to exhibit some agonistic activity (Gazi et al 1998(Gazi et al , 1999. In contrast, 2-[4-(4-chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 213) was shown to be not only highly D 4 selective (Table 1), but also a complete antagonist with less than 3% agonistic activity compared with the full agonist quinpirole (Löber et al 2001).…”
Section: Introductionmentioning
confidence: 99%